Sight distance analyses in road design process: Serbian practice - Gavran, Dejan; Fric, Sanja; Ilić, Vladan; Trpčevski, Filip (Transport, 2016)
New Serbian policies on road design introduce the concept of operating speeds. Decades ago, national policies were based on the constant design speed concept. Among other design parameters, in relation to that constant design speed, minimum radii of horizontal and vertical road geometry were determined. Introduction of the operating speed concept provides for more realistic prediction of speed levels along the road. Unlike the constant design speed, operating speed levels vary along the road, reaching higher levels in curves with larger radii, on straight sections and on reverse curves and dropping down to the design speed level in horizontal curves with the minimum radius. Consequently, besides a constant Stopping Sight Distance (SSD), which is calculated from the constant design speed, the new term, Required Sight Distance (RSD) is introduced. RSD varies along the road, as it is calculated from the operating speed, which also varies along the road. Appropriate RSD analyses are crucial on road rehabilitation projects, since a simple resurfacing that enables higher speed levels, without providing increased RSD, may hamper the safety of a newly resurfaced road. Software tools for predicting operating speed levels and optical analyses of the road are also presented in this paper. Software tools for RSD analyses enable the import of lines of sight into the 3D model of the roadway and their export into the cross sections extracted from the model, thus facilitating the obstacle removal. Also demonstrated are tools for determining Available Sight Distance (ASD), which are based on triangulated 3D models of the roadway as well.